Synthesis of Corrosion Inhibitor IKPK-1 and its Application for Corrosion Protection of Steel ST20 in 1M HCL (Eurasian Journal of Engineering and Technology, 2022)
In this paper, the synthesis of IKPK-1 corrosion inhibitor based on pphenylenediamine and crotonaldehyde was studied. When the initial feed was taken in a ratio of 1: 2, it yielded higher yields than those obtained in other ratios. The IR spectra of the obtained corrosion inhibitor were studied. The obtained corrosion inhibitor is a gravimetric method with different concentrations (100 mg / l to 400 mg / l) and inhibition efficiency at different temperatures (298, 313 and 323 K) and the braking coefficient (γ), the surface temperature (θ), the degree of protection (η) values were determined.